2022
DOI: 10.14254/2071-789x.2022/15-3/11
|View full text |Cite
|
Sign up to set email alerts
|

Strategic orientation of companies: The several strategic issues in times of COVID-19 pandemic

Abstract: Has companies’ strategic orientation become more important in times of crisis due to the COVID-19 pandemic? Do companies feel the need to work strategically, and what impact can strategic management have on a company's profitability? The objective of the paper is to find out what features differ profitable companies from less profitable or loss-making companies in the current times from the view of strategic management. Features such as (1) the importance of vision; (2) orientation of strategic goals; (3) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…In addition, the decision to work together with food aggregators like Foodpanda and GrabFood helped revitalise and sustain their business. These findings corroborate the ideas of Lesníková et al (2022), who suggested that strategic management actions are critical in the business world for establishing new directions for long-term survival, stability, and expansion, even during times of crisis. For the MFFB owners, switching from catering to providing direct food sales was key to building a long-term, sustainable business.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the decision to work together with food aggregators like Foodpanda and GrabFood helped revitalise and sustain their business. These findings corroborate the ideas of Lesníková et al (2022), who suggested that strategic management actions are critical in the business world for establishing new directions for long-term survival, stability, and expansion, even during times of crisis. For the MFFB owners, switching from catering to providing direct food sales was key to building a long-term, sustainable business.…”
Section: Discussionsupporting
confidence: 88%
“…These processes are determined by entrepreneurial orientation (Belas & Sopkova, 2016;Horobet et al, 2022) and the quality of the business environment in the SME segment (Belas et al, 2019). Besides, they should be considered in companies' strategic management (Lesníková et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…2021;Muangmee et al, 2022). The knowledge management systems within the HRM should be aligned with the overall strategic aim of the business (Lesníková et al, 2022). To achieve the strategic goals, enterprises try to increase the effectiveness of knowledge sharing via vocational training (Samoliuk et al, 2021) and overall changes in the learning orientation of firms (Meekaewkunchorn et al, 2021).…”
Section: Introductionmentioning
confidence: 99%